The frequency of mutations in advanced thyroid cancer in Japan: a single-center study - Soji Toda; Hiroyuki Iwasaki; Yoichiro Okubo; Hiroyuki Hayashi; Mei Kadoya; Hiroyuki Takahashi; Tomoyuki Yokose; Yukihiko Hiroshima; Katsuhiko Masudo (Endocrine Journal)
We analyzed the outcomes of genetic testing to study the frequency of mutations in advanced thyroid cancer in Japan. Patients (n = 96) with unresectable or metastatic thyroid carcinoma were included for retrospective chart review. Results of gene panel testing, which was performed between May 2020 and April 2023, were analyzed. The median age of the patients was 73.5 years (range, 17–88); 59 were women, and 39 were men. Overall, 17 patients had anaplastic thyroid carcinoma (ATC), 68 had papillary thyroid carcinoma (PTC), 7 had follicular thyroid carcinoma, and 6 had poorly differentiated thyroid carcinoma (PDTC). Of the 81 patients with differentiated thyroid carcinoma (DTC) and PDTC, 88.9% were radioactive iodine-refractory, and 32.7% of all cases had previously been treated with multiple kinase inhibitors. Of ATC cases, 52.9% had BRAF mutations, and 5.9% had RET fusion. Of PTC cases, 83.1% had BRAF mutations, 9.2% had RET fusion, and 1.5% had NTRK fusion. One case each of ATC and PTC had a tumor mutation burden of ≥10. ATC cases had a significantly higher prevalence of TP53 alterations than the other cases (82.3% vs. 11.8%), whereas the frequencies of TERT promoter mutations were 88.2% in ATC cases and 64.7% in the other cases, albeit without a significant difference. In conclusion, 58.8% of ATC, 93.8% of PTC, and 42.9% of PDTC had genetic alterations linked to therapeutic agents. Active gene panel testing is required to increase treatment options.